Efficacy of Transcutaneous Electrical Nerve Stimulation for Management of Osteoarthritis of Knee Joint: A Randomized Control Trial (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Management of osteoarthritis of knee joint is very important.Objective: The purpose of the present study was to observe the efficacy of transcutaneous electrical nerve stimulation (TENS) in the treatment of osteoarthritis (OA) of the knee.Methodology: This study was designed as randomized control trial which was conducted in the Department of Physical Medicine at Dhaka Medical College Hospital, Dhaka Bangladesh from July 2007 to December 2007 for a period of six (06) months. Patients presented with osteoarthritis at the age group of more than 30 years to 60 years with both sexes who were attended in Physical Medicine and Rehabilitation department in the Dhaka Medical College Hospital, Dhaka were selected as study population. The study populations were included by purposive sampling method after fulfilling the inclusion and exclusion criteria and were divided into two groups designated as intervention group (group A) and control group (group B). Group A was treated with TENS, therapeutic exercise, NSAID and ADL. Group B was treated with therapeutic exercise, NSAID and ADL.Results: A total of 60 patients with osteoarthritis (OA) of the knee joint were included in the study group. The mean age of both sexes were 46.67±7.04 years and male (46.83±7.73) patients were higher than female (46.56±6.41). There was significant difference in improvement of pain between two groups after treatment for two week (p=0.002); however, finally it was found that there was no significant difference in improvement of pain between two groups after treatment for 6(six) weeks. There was no significant difference in improvement of range of movement (ROM) between two groups after treatment for six weeks (p=0.946). There was no significant difference in improvement of walking speed between two groups after treatment for six weeks (p=0.611).Conclusion: In conclusion significant decrease of pain with increase of ROM and walking speed is found in all patients group with OA knee regardless of the treatment program.Journal of National Institute of Neurosciences Bangladesh, 2017;3(2): 75-79